2021
DOI: 10.7759/cureus.20632
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Andexanet Alfa for Bleeding Caused by Factor Xa Inhibitors: A Systematic Review and Meta-Analysis

Abstract: Direct oral anticoagulants (DOAC) including factor Xa inhibitors are associated with bleeding events which can lead to severe morbidity and mortality. Reversal agents like andexanet alfa (AA) and 4F-PCC (Four-factor prothrombin concentrate complex) are available for treating bleeding that occurs with DOAC therapy but a comparison on their efficacy is lacking. In this study, we analyzed the efficacy and safety of patients treated with andexanet alfa for bleeding events from DOAC. Databases were searched for rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…Shrestha et al, 32 a systematic review and meta-analysis of 1245 studies published in 2021, concluded andexanet alfa reduced in-hospital mortality in patients who had bleeding attributed to factor Xa inhibitors compared to 4F-PCC. There was no statistical difference in thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…Shrestha et al, 32 a systematic review and meta-analysis of 1245 studies published in 2021, concluded andexanet alfa reduced in-hospital mortality in patients who had bleeding attributed to factor Xa inhibitors compared to 4F-PCC. There was no statistical difference in thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…1 Only two MAs specifically pooled comparative studies of andexanet alfa versus PCC products, and additional comparative studies have since been published. 1,14 Previous MAs also did not systematically evaluate the risk of bias within each included study and the impact of including studies with high risk of bias on the results, nor was appropriate caution applied when interpreting the results. 1,[7][8][9][10]14 The inclusion of studies at high risk of bias in a MA may distort the observed effect away from the true effect.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…with rationales for the ratings. 1,14 The Shrestha 2021 MA included only three studies (Ammar 2021, Barra 2020, Coleman 2021). 14,28,29,31 The most recent systematic review by Chaudhury had a high risk of bias.…”
Section: Agreement Among Raters For Risk Of Bias Determinations In In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Die Evidenzlage bezüglich thromboembolischer Komplikationen je nach dem Gegenmittel ist nicht eindeutig. Einige Studien konnten keine signifikanten Unterschiede zwischen dem Thromboembolierisiko nach Andexanet-alfa-und PPSB-Gabe finden [41,42]. In der Metaanalyse von Gómez-Outes et al waren Thromboembolien nach Andexanet-alfa-Gabe jedoch signifikant häufiger (10,7%) im Vergleich zum generellen Thromboembolierisiko nach allen 3 untersuchten Gegenmitteln (Andexanet alfa, Idarucizumab, PPSB; 4,6%) Dies beruht möglicherweise auf einem prothrombotischen Rebound-Effekt, da Andexanet alfa vorübergehend die Thrombinproduktion steigern kann [38].…”
Section: Merke Bei Patienten Mit Icb Unter Apixaban Oder Rivaroxaban ...unclassified